Analisis Commissioning Pembangkit Listrik Tenaga Surya Kapasitas 20.5 kWp On Grid PT. Quickprint Office - Soedjarwanto, Noer; T Rausyan Hilmy; Komalasari, Endah; Zebua, Osea (Jurnal Teknik Ilmu dan Aplikasi, 2024)
Solar power plants (PLTS) are one of the renewable energy plants that continue to be developed in Indonesia to meet electrical energy needs. The Indonesian government issued the Electricity Supply Business Plan (RUPTL) as a national energy management framework designed to resolve energy needs challenges and problems by utilizing new renewable energy sources (EBT). In the construction of a Solar Power Plant (PLTS) at PT. Quick Print Office built PLTS with a capacity of 20.5 kWp which is used for the electrical energy needs used by PT. Quick Print Office with a total power of 10 kWp, generator system with an on grid system which means it is directly connected to the PLN network. In the feasibility study, the performance ratio (PR) obtained from manual calculations for inverter 1 was 71.9% and inverter 2 was 26.2%. Meanwhile, to improve the performance ratio of the PLTS system, maintenance of the PLTS system is required, starting from cleaning the panels or checking the cable installation on the PLTS. For the calculation results, the efficiency on inverter 1 was 94.6% and on inverter 2 the efficiency was 90.8% when measured at 11.18 – 14.53.